Motivation management model and practical realization within the health care institutions - Alla Mamay; Iuliia Myroshnychenko; Henryk Dzwigol (Health Economics and Management Review)
The motivation of medical workers is essential to society since the quality of their work affects the individual and public health. The authors highlighted the special role of state and municipal authorities in motivating medical professionals. The study aims to identify the main directions and elaborate the recommendations to build motivational management models in health care facilities. The study reveals the essence and objectives of personnel policy management in health care facilities. The main methods of motivating health workers were analyzed. The authors evaluated the impact of health reforms on health workers' motivation. The study proposed several ways to improve the motivational management models. The authors conducted an in-depth analysis of economic and non-economic motivation in health care facilities. The methodological basis of the study is comparative analysis, the method of scientific abstraction, induction and deduction analysis, and synthesis. The practical implementation involved the online services Google Ngram Viewer and SciVal. The findings proved the need to develop the health care quality performances and their approval at the local level. The authors concluded that it is necessary to elaborate on a local program of employees' motivation of utility non-profit enterprises to implement qualitative indicators. This program may include the mayor's award, awards free internship programs, invitations to cultural events, symbolic gifts, etc. The obtained results showed that the health reform didn't cover all activity areas of the health care institutions while the funding for medical care per one patient was insufficient. Therefore, the study emphasized the urgency to solve the above strategic problem in state and municipal management in Ukraine. The findings could be useful for the state and the municipal government of Ukraine in elaborating on motivation programs for health workers and their maintenance.